Phosphorylation of ASPP2 by RAS/MAPK pathway is critical for its full pro-apoptotic function - Godin-Heymann, N; Wang, Y; Slee, E; Lu, X (Public Library of Science, 2013)
We reported recently that apoptosis-stimulating protein of p53 (ASPP) 2, an activator of p53, co-operates with oncogenic RAS to enhance the transcription and apoptotic function of p53. However, the detailed mechanism remains unknown. Here we show that ASPP2 is a novel substrate of mitogen-activated protein kinase (MAPK). Phosphorylation of ASPP2 by MAPK is required for RAS-induced increased binding to p53 and increased transactivation of pro-apoptotic genes. In contrast, an ASPP2 phosphorylation mutant exhibits reduced p53 binding and fails to enhance transactivation and apoptosis. Thus phosphorylation of ASPP2 by RAS/MAPK pathway provides a novel link between RAS and p53 in regulating apoptosis.